SISTEM PENDATAAN BARANG YANG MASUK KE GUDANG SECARA OTOMATIS MENGGUNAKAN MEDIA BARCODE - Hugeng Hugeng; Muljono Muljono; Hery Iskandar (Jetri : Jurnal Ilmiah Teknik Elektro, 2013)
Abstract Warehouse is an inseparable part in the trading business. Warehouse management systems, particularly distribution warehouse is usually done manually, such as collection of goods entering into the warehouse and grouping goods according to its type. This method is felt less effective and efficient as it can cause a collection of errors due to inaccurate calculations. This problem then becomes the basis of design model of collection of goods system that enter into the warehouse automatically using barcode media, where the barcode contains information of goods. Collection of goods is done by reading a barcode through the barcode scanner that is connected with a Personal Computer connected to the microcontroller to drive the conveyor and sliding motor that controlled by motor drivers for collection and grouping goods according to its type automatically. Goods can be grouped according to its type after collection of goods through the barcode scanner. Keywords: warehouse, collection of goods, barcode